The Effectiveness of Productive ZIS Movements Based on Local Wisdom “Can Coins” Towards The Economy of The Society of Malang District - Vika Annisa Qurrata; Qurrotu Ayniy Ayniy; Riqa Aniqa Helma Alam (MediaTrend, 2022)
The purpose of this study is to determine the economic impact of the productive zakat infaq sodaqoh (ZIS) movement based on indigenous wisdom and the use of "coin cans" on the residents of Simping Village, Malang Regency. The Zakat Collector Network (JPZIS) carried out the program campaign for ZIS in Simping Village, Malang Regency. It is one of the local non-profit organizations under the guidance of Lazis NU which accommodates the receipt, management, and distribution of zakat and infaq for the local community with the program "coin cans." This study used a quantitative descriptive method through allocation to collection ratio (ACR) and a logit test. This study uses data from the financial statements of the JPZIS Simping Village, Malang Regency, and the people who have received this program. The results showed that the productive ZIS movement program "coin cans" using the ACR method effectively distributes it. Additionally, the logit test indicates that distribution effectiveness has a positive and significant effect on recipients' income, consumption, and education. The community primarily uses the effect of this income to cover basic daily expenses and school tuition. On the basis of the foregoing analysis, it can be concluded that the ZIS movement is based on indigenous wisdom. If managed professionally and effectively, many regions can use it to boost their local economies.